A Research Drawn on Housing and the City. A Conversation with Orsina Simona Pierini - Salvo, Simona; Cervero Sánchez, Noelia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The research and teaching activity of Orsina Simona Pierini, Professor of Architectural and Urban Composition at the Department of Architecture and Urban Studies of the Polytechnic University of Milan, focus on the historical interpretation of the city’s architecture from the perspective of design. Her knowledge of the role of the dwelling in urban planning stems from the systematic study of the different expressions of habitation in contemporary European cities, as well as from specific research focused on modern Spanish architecture and Milanese residential constructions, with particular attention to the relationship between the dwelling and the city. Her interpretation of these phenomena is, therefore, transversal as it involves various different scales and addresses the critical-historical sphere; it’s also a means to define design methods that respond to the needs and demands of current habitation. This conversation with Orsina Simona Pierini is organised, therefore, around certain topics that summarise her experience as a scholar and her personal opinion of the expressions of contemporary collective architecture that define the configuration of the contemporary city and, in general, the current way of inhabiting.